Trapping of soluble, KCl-stabilized Cu(i) hydrides with CO2 gives crystalline formates - Grasruck, Alexander; Parla, Giorgio; Lou, Lisha; Langer, Jens; Neiß, Christian; Herrera, Alberto; Frieß, Sibylle; Görling, Andreas; Schmid, Günter; Dorta, Romano (Chemical Communications, 2023)
Cu(i)-Hydrido complexes supported by dibenzo[b,f]azepinyl P-alkene hybrid ligands and stabilized by electrostatic interactions in a Cu-H⋯KCl⋯BR3 arrangement can be trapped with CO2 at low temperature to afford Cu(i)-formates. The complexes are isolable with and without a pendant BEt3 group and show strong Cu-O and weak B-O interactions.
CRIS-Team Scopus Importer:2023-12-15